2008
DOI: 10.1111/j.1750-3841.2008.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties as Affected by Laboratory‐Scale Parboiling of Rough Rice and Brown Rice

Abstract: Rough rice (RR) is the conventional feedstock for parboiling. The use of brown rice (BR) instead of RR is gaining interest because it results in shorter processing time and lower energy requirement. This study compared the functional properties of milled parboiled rice under different parboiling conditions from RR and BR. Presoaked RR and BR from cultivars Bolivar, Cheniere, Dixiebelle, and Wells were parboiled under mild (20 min, 100 degrees C, 0 kPa) and severe (20 min, 120 degrees C, 98 kPa) laboratory-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 26 publications
16
74
0
Order By: Relevance
“…The authors have attributed such effect to greater degree of gelatinization reached during grain cooking. More recently, Patindol et al (2008) have also observed that pressure parboiling of rice significantly improves the performance of milling yields.…”
Section: Milling Yieldsmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors have attributed such effect to greater degree of gelatinization reached during grain cooking. More recently, Patindol et al (2008) have also observed that pressure parboiling of rice significantly improves the performance of milling yields.…”
Section: Milling Yieldsmentioning
confidence: 96%
“…Manful et al (2008), who investigated rice parboiling, reported partial gelatinization with GD of 68 %. Patindol et al (2008) produced partially gelatinized rice with gelatinization percentages in the range of 13 to 42 %. These authors, in contrast to the present work, have controlled the gelatinization degree by setting process time in conventional rice parboiling.…”
Section: Thermal Parametersmentioning
confidence: 99%
“…Besides, formation of melanoidin compounds in Maillard reaction between reducing sugars from the heated starch and the amino group in the proteins on high heat processing [19]. The decreased in total starch and amylose contents is attributed either to the leaching out of starch and amylose into the soaking water [23]. Or the more severe the processing condition/ gelatinization process, the more rapid the digestion of starch, the more decrease in soluble amylose [45,46].…”
Section: Chemical Composition Of Broken Rice Flour and Untreated And mentioning
confidence: 99%
“…On parboiling, the starch granules are gelatinized, retrograded, and considerable changes occur in the pasting parameters due to the orderdisorder transitions taking place at the molecular level [20,22]. These changes play an important role in the subsequent processing operations, such as, cooking and eating qualities [23,24]. Popping in the presence of salt solutions is another hydrothermal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It affects the physical properties of rice, nutritional composition, starch characteristics (sticking properties and crystallinity), cooking qualities, etc. [41,6,11,42,43,32]. According to these authors, the purpose of parboiling is to produce physico-chemical and organoleptic modifications that are advantageous from an economic, nutritional and practical point of view.…”
Section: Impact and Nutritional Intake Of Rice Parboilingmentioning
confidence: 99%